C56. Isolated Right Ventricular Non-Compaction Cardiomyopathy (IRVNC) in Adolescence: A Case Report. (23rd November 2021) - Fernandes, R; Lukito, A A; Chandra, S; Hutabarat, H
Abstract: Background: Non-compaction ventricular myocardium (NCVM) is a rare genetic cause of cardiomyopathy which mostly affects the left ventricle. A limited case of IRVNC was reported which render a limited knowledge for clinician. Case Summary: A 16-y.o male presented to our emergency unit with recurrent syncope, chest discomfort, palpitation which exaggerated by strenuous exercise. There was no familial history of sudden death. On admission, BP of 102/64 mmHg and bradycardia of 49 bpm were remarkable. Electrocardiography revealed sinus arrhythmia, 49 bpm with early repolarization on precordial leads and LVH. Laboratory tests were in normal limits. Echocardiography revealed hyper-trabeculated RV with no LV-dysfunction. CMR was performed and showed normal LV dimension and function. Right atrium and RV were dilated with RV-dysfunction. RV trabeculae were indicative for IRVNC (NC/C ratio of 4.3). Holter ECG monitoring was done and remarkable for sinus arrhythmia without sinus pause nor ventricular arrhythmia. Anticoagulant was given for embolic prevention in the non-compacted area. ACEi, β-blockers, and diuretic were not given due to hypotension, bradycardia and no signs of congestion. The patient showed clinical improvement and discharged after 5 days of hospitalization. Discussions: Recently, there has been no specific criteria and cut off for IRNVC. Earlier studies mentioned that ILVNC criteria could be used for diagnosing IRNVC, as we used in our case. In the future, it's necessary to determine new cut off points dedicated for IRVNC. Furthermore, close follow-up is needed as complications such as arrhythmia, embolic events and heart failure might occurred.